If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -29 + 2x + 24 = 67 Reorder the terms: -29 + 24 + 6x + 2x = 67 Combine like terms: -29 + 24 = -5 -5 + 6x + 2x = 67 Combine like terms: 6x + 2x = 8x -5 + 8x = 67 Solving -5 + 8x = 67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 8x = 67 + 5 Combine like terms: -5 + 5 = 0 0 + 8x = 67 + 5 8x = 67 + 5 Combine like terms: 67 + 5 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| 4(1+8v)+5v=-255 | | 8y+25=4y-27 | | 4(1+8)+5v=-255 | | 2x-9-5x=17-3x-42+8x | | (1-v)(3v-7)=0 | | (6x^2+7x-3)-(-2x^2+4x-5)= | | y=3(2x+4) | | 4x^2-3x+7+2x^2+4x= | | 95=0.05s^2+1.1s | | 2(y-1)=3y+4 | | 0.75-18.50=0.65x | | 2f-6=2 | | 2x+12y=-1 | | 14+C=22 | | E=(8+5)*3 | | 5-5b+7=-18 | | c+14=22 | | 5-5b+7=-8 | | x*x+2x=8 | | 10+0.10x=12+0.05x | | 2+ -4= -2 | | 12x(4+3)= | | 6x-30=5y | | 2x^2-8x+2y+18=0 | | -3(y+6)=-6y-48 | | 5y+66=16y-3y+54 | | 1,500=-475x+2,650 | | 3x+2-7x=-42 | | X^3-6x^2+13x=10 | | -3(r+2)=-47 | | 2-8k+8=-6 | | -3y-39=-6(y+6) |